Día de los Muertos - Salazar, Alicia, 1973- (Traditions and celebrations (Pebble (Firm)), 2022)
Día de los Muertos is a special holiday to remember and celebrate loved ones. It is a Mexican tradition held to honor those who have died. Some people dress up and go to parades. Others sing, dance, and eat special food. Others decorate altars with flowers and make offerings. Readers will discover how a shared holiday can have multiple traditions and be celebrated in all sorts of ways.